MNAT PESERTA DIDIK DENGAN HAMBATAN PENDENGARAN UNTUK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI - Nur Tyara Fajarwati, - (2020)
To gain higher education is the right of all people without exception, including children with hearing obstacle. Interest factor becomes very important to fulfill their hope to continue education of higher education. Therefore, this research aimed to know (1) students' with hearing impairment interest to continue education of higher education, (2) Factors that influence students' with hearing impairment interest to continue education of higher education. This research used qualitative approach with descriptive method. Data collecting technique did by interview and documentary study. This research result showed that from four subjects researched there are two subjects of SMALB SLB BC YP Al-Azhar Leuwimunding that interest to continue education of higher education, this case can be seen from the happiness and interested to study subjects such as cosmetology and the art of dance that based on the subject's dreams. Furthermore, the subject's interest to continue of higher education caused by internal factor such as motivation inside subject and external factor such as parents' support, teacher and social friends. Recommendations of this research those are to parents hopefully communicate with Teacher to give motivation to students. Teachers hopefully able to give further information on higher education. Keywords: Interest, Students with Hearing Impairment, Higher Education